METABOLIC SYNDROME MARKERS AT TEENAGERS WITH ESSENTIAL ARTERIAL HYPERTENSION AND GALL BLADDER DYSFUNCTION - G. J. Nagornaya; Z. I. Mikashinowich; T. D. Kovalenko (Медицинский вестник Юга России, 2014)
Purpose: To estimate the appearance frequency of metabolic syndrome (MS) markers at teenagers with essential arterial hypertension (EAH) and biliary dyskinesia to reveal its importance as risk factors of this nosologic syntropy.Materials and Methods: 50 teenagers at the age from 13 to 16 years were examined. Level of glucose, uric acid, cholesterol (ChS), ChS of high density lipoproteins (HDL), ChS of low density lipoproteins (LDL) and ChS of very low density lipoproteins (VLDL), concentration of triacylglycerides (TAG), the level of Willibrandt factor, the cortisol level were estimated in the serum of blood of all examined teenagers (on the empty stomach)Results: Momomarkers of MS were found at 38 teenagers with EAH and biliary dyskinesia, that consisted 76% among all examined teenagers.Summary: Teenagers with biliary dyskinesia on the early steps of EAH formation had both and monomarkers of MS and their combination.